In-vitro and ex-vivo antidiabetic, and antioxidant activities of Box-Behnken design optimized Solanum xanthocarpum extract loaded niosomes - Rama Tyagi; Ayesha Waheed; Neeraj Kumar; Mohd. Mujeeb; Tanveer Naved; Mohammad Rashid Khan; Khaled Alhosaini; Yasser A. Alqarni; Rani Rahat; Perwez Alam; Swati Madan (Elsevier, 2023)
One of the most prevalent lifestyle diseases, diabetes mellitus (DM) is brought on by an endocrine issue. DM is frequently accompanied by hyperglycemia, a disease that typically results in an excess of free radicals that stress tissues. The medical community is currently concentrating on creating therapeutic medications with roots in nature to lessen the damage associated with hyperglycemia. Solanum xanthocarpum has a number of medicinal benefits. The investigation aimed to produce and analyze niosomal formulations containing S. xanthocarpum extract (SXE). Niosomes were made by implementing the solvent evaporation process, which was further optimized using Box-Behnken design. Drug release, DPPH assessments, α-amylase inhibition assay, α-glucosidase inhibition assay, and confocal laser scanning microscopy (CLSM) investigation were all performed on the developed formulation (SXE-Ns-Opt). SXE-Ns-Opt displayed a 253.6 nm vesicle size, a PDI of 0.108, 62.4% entrapment efficiency, and 84.01% drug release in 24 h. The rat's intestinal CLSM image indicated that the rhodamine red B-loaded SXE-Ns-Opts had more intestinal penetration than the control. Additionally, the antioxidant effect of the obtained formulation was demonstrated as 89.46% as compared to SXE (78.10%). Additionally, acarbose, SXE, and SXE-Ns-Opt each inhibited the activity of α-amylase by 95.11%, 85.88%, and 89.87%, and also suppressed the enzyme of α-glucosidase by 88.47%, 81.07%, and 85.78%, respectively. To summarise, the establishment of the SXE-Ns-Opt formulation and its characterization demonstrated the legitimacy of the foundation. A promising candidate for the treatment of diabetes mellitus has been shown as in vitro studies, antioxidant against oxidative stress, CLSM of rat's intestine and a high degree of penetration of formulation.